Quantification of Urea-spray Non-uniformity Effects on the H2-assistedNO Reduction and NH3 Slip over an Ag/Al2O3 Catalyst. (August 2015) - Ström, Linda; Ström, Henrik; Darnell, Andreas; Carlsson, Per-Anders; Skoglundh, Magnus; Härelind, Hanna
Abstract: Selective catalytic reductionof nitrogen oxides (NOx ) with ammonia (NH3 -SCR) is an efficient technology for lean NOx removal in automotive applications. In the current work, a kinetic model forhydrogen-assisted NH3 -SCR over a silver-alumina (Ag/Al2 O3 ) monolith catalyst is adapted to the corresponding experimental results. The degree of non-uniformity in the NH3 dose to individual catalyst channels during operation of a urea-SCR system is also investigated and the NH3 dose probability distribution functions are derived. The effects ofNH3 non-uniformity on the NO conversion and NH3 slip are studied over an otherwise optimal Ag/Al2 O3 system. Above the stoichiometric point, the NH3 slip is shown to increase almost linearly with increasing NH3 dosage. Channels that receive significantly lower NH3 dose than the stoichiometric one exhibit low NO conversion, whereas there is no discernable increase in the NO conversion above an NH3 dose four times the average. These results highlight the importance of the interaction between the design of the NH3 dosing system and the performance of the catalytic system.